Perceptions of adult literacy policy and practice: A survey of leaders in the field - Robert L. Dilworth (Adult Education Research Conference, 1995)
Research encompassed 115 interviews of key opinion leaders in surveying perceptions of adult literacy policy and practice, with special focus on the period surrounding passage of the National Literacy Act of 1991.